Effect of A High-Density Street-Level on Air Temperature in Outdoor Space of Neighborhoods of Hot, Dry Cities - Rami Qaoud; Youcef Kamal; Alkama Djamal (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2022)
The outdoor spaces of residential neighborhoods are an important part of residents' lives the outdoor spaces in the neighborhood are fundamental for the social life due to their capacity to serve as meeting spaces and interactions among the public, here comes this search, which is based on study of the role of highdensity –street level- on air temperature in outdoor space of neighborhoods. The methodology was based on three parts, initially, determine the sample which is three downtown residential neighbourhoods according to scientific criteria. secondly, conducting a field survey of climatic factors (air temperature - relative humidity - wind speed) thirdly, make a model to simulate the built environment by using the envi-met 4.4.6 program, according to the data of the survey, the results indicated that significant variations of value of DSR, MRT, AT variables among residential neighborhoods which points the effect of high-density street-level on air temperature in outdoor space.